School management in improving quality education in SMA Nurul Ilmi Padangsidimpuan - Dunia Siagian; Kasman Rukun; Sufyarma Marsidin; Syafri Anwar (International Conferences on Educational, Social Sciences and Technology)
The school management can mean everything pertaining to the management of the educational process to achieve the stated goals, both short-term goals, medium, or long-term goals. The purpose of term goal of this research was to determine the school management to improve the quality of education, to include: (1) Planning school programs; (2) The implementation of school programs and (3) Barriers faced. This study used a qualitative approach with descriptive methods. Subjects were principals, supervisors and teachers in primary schools Boarding School Jar Pidie district. Research results found: (1) planning school programs, (2) The implementation of school programs, and (3) Barriers in planning school programs. It is expected that supervisors in order to direct and supervise principals in improving the quality of education on school program planning, program implementation and obstacles faced by appropriate, effective and efficient so that the quality of education in the schools can be improved.